Analisis Struktur dan Perencanaan Ketahanan Gempa (SNI 1726:2012) Warehouse PT. X di Gresik - Akhmad Andi Saputra; Dandy Nugroho; Ahmad Muwafiqudinulhaq (Wahana Teknik, 2020)
Warehouse is a building to store a variety of necessary products for a company, it could be said that warehouse is collection point and starting point of the goods that will be distributed to the retailer or directly to the consumer. In cases that took place at the warehouse in PT.X is a building which had height of 26 meters and span of 25 meters that has earthquake-prone and wind loads. This makes researcher need to do structure analysis and planning of warehouse resilience of PT.X in Gresik.This study uses SNI 1726:2012 for planning earthquake resistance of building and non-building structures. The step of structure analysis of rafters, gordings, beams and columns as follows: 1. Input data into STAAD pro (structure modelling), 2. Control the strength of rafter structures, gordings, beams and columns using the largest external force data based on calculations from STAAD pro.The results of this study are: 1. The structural resistance to combined loads according to SNI 1726:2012 shows an indication of the inability of the steel profile on the H 350 x 175 rafter and on the H 250 x 125 beam with the actual value of the allowable ratio more than 1.00, 2. The rafter profile is replaced with I 450 x 175 x 11 profile which has a ratio value of 0.7818 and the beam profile is replaced with H 250 x 250 x 9 x 14 which has a ratio value of 0.1996, both steel profiles have indicated pass result. Keywords: Analysis, STAAD Pro, Steel, Structure.